A microfluidic platform for size-dependent generation of droplet interface bilayer networks on rails - Carreras, P. (Biomicrofluidics, 2015)
Droplet interface bilayer (DIB) networks are emerging as a cornerstone technology for the bottom up construction of cell-like and tissue-like structures and bio-devices. They are an exciting and versatile model-membrane platform, seeing increasing use in the disciplines of synthetic biology, chemical biology, and membrane biophysics. DIBs are formed when lipid-coated water-in-oil droplets are brought together—oil is excluded from the interface, resulting in a bilayer. Perhaps the greatest feature of the DIB platform is the ability to generate bilayer networks by connecting multiple droplets together, which can in turn be used in applications ranging from tissue mimics, multicellular models, and bio-devices. For such applications, the construction and release of DIB networks of defined size and composition on-demand is crucial. We have developed a droplet-based microfluidic method for the generation of different sized DIB networks (300–1500 pl droplets) on-chip. We do this by employing a droplet-on-rails strategy where droplets are guided down designated paths of a chip with the aid of microfabricated grooves or “rails,” and droplets of set sizes are selectively directed to specific rails using auxiliary flows. In this way we can uniquely produce parallel bilayer networks of defined sizes. By trapping several droplets in a rail, extended DIB networks containing up to 20 sequential bilayers could be constructed. The trapped DIB arrays can be composed of different lipid types and can be released on-demand and regenerated within seconds. We show that chemical signals can be propagated across the bio-network by transplanting enzymatic reaction cascades for inter-droplet communication.